Optimization of Mango Peel Size in Eco-enzyme with Molasses as Carbon Source - Shalihah, Nuha Fathinah; Firlianti, Sekar Putri; Hardhaneszha, Azkaifa Syawqie; Djuarsa, Peristiwati (HIGIENE: Jurnal Kesehatan Lingkungan, 2024)
Background: Eco-enzyme is one of the products of the fermentation process that has many benefits by utilizing organic waste such as mango peels. Putpose: This study aims to determine the differences in characteristics of eco-enzyme made from mango peel waste of different sizes during fermentation. Method: This research was conducted in three stages: eco-enzyme fermentation, organoleptic testing, and quantitative testing. The variations in mango peel sizes used were small (1x2 cm), medium (2x4 cm), and large (4x8 cm). Organoleptic testing was performed on 10 panelists using predetermined parameters, including aroma and color evaluation of the eco-enzyme. Quantitative testing was carried out by measuring the pH of the eco-enzyme using a pH meter. All tests were conducted on 3 different eco-enzyme treatments with 3 replicates, and the eco-enzyme was harvested on the 35th day. Results: Organoleptic testing revealed that the eco-enzyme made from the smallest mango peel size (1x2 cm) had higher scores in terms of aroma and color compared to the eco-enzyme made from larger peel sizes. Meanwhile, the quantitative testing showed that the eco-enzyme with the 1x2 cm peel size had the most acidic pH. In this eco-enzyme production, beneficial pitera mushrooms for the skin were also obtained. Conclusion: In this mini research, it was found that the best eco-enzyme was produced using the smallest mango peel size (1x2 cm), which resulted in the most acidic pH, the best aroma score of 2.6, and the best color score of 2.7. Suggestion: Further research is needed to determine if the results are similar between mango peel and other fruit peels in terms of size.